Evaluation of the rotational stiffness and visco-elasticity of the low back and improving the low back visco-elasticity. (9th May 2011) - Chaudhry, Hans; Atalla, Nadi; Singh, Vishal K.; Roman, Max; , Thomas Findley
An automated anatomical torsion monitor (A-ATM) is developed to evaluate the stiffness and visco-elasticity of the low back as a static load is applied and removed from the pelvis. The resulting hysteresis loop area (HLA) is used to evaluate the mechanical properties of the low back. Also a technique for improving the low back dysfunction by imparting oscillations to the low back is presented. The before and after HLAs are compared for objective evaluation. It is observed that providing oscillations to the low back for five minutes at a frequency of 20 cycles per minute results in improved elasticity of the low back for those subjects whose BMI is 25 or less and an insignificant change in stiffness for all the subjects. However the correct displacement amplitude, frequency, and duration of treatment will depend upon individual medical and physical conditions.